Life Cycle Assessment in Road Pavement Infrastructures: A Review - Bruno Guida Gouveia; Marina Donato; Marcelino Aurélio Vieira da Silva (Salehan Institute of Higher Education, 2022)
The need to meet society's demands for road infrastructure while minimizing the resulting environmental impacts is a source of great complications. In this context, Life Cycle Assessment (LCA) can be useful by applying a set of rules and processes for the environmental assessment of projects. The objectives of this study were to present the main environmental impact categories associated with emissions from the life cycle phases of a road pavement and how to estimate them. In addition, this paper provides examples of LCA applications on these infrastructures. In view of the evolution of research on LCA, a compilation was made on: the main categories of environmental impact associated with emissions; phases of life cycle impact assessment; and procedures and methods of impact estimation. The impact categories presented are associated with climate change, acidification, ozone depletion, tropospheric ozone formation, eutrophication, and Particulate Matter Formation. Not all methods are able to generate indicators for all types of impact and, depending on the type of materials and services that make up the inventory of the alternatives analyzed, one specific method may be more appropriate to use. The conclusions are that for each environmental impact, the results depend on the input parameters, such as energy flows and materials, along with their processing by methods of life cycle impact assessment. Besides this, despite the great diversity of the databases for the steps of life cycle assessment of roadway pavement, there is a general consensus about the nature of these steps. Doi: 10.28991/CEJ-2022-08-06-015 Full Text: PDF